Formulation and Evaluation of Polyherbal Face Scrubber for Oily Skin in Gel Form (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Cosmetics play a vital role for everyone to have a joyful and sanguine life. In present scenario herbal cosmeceuticals have more demand because they have no side effects. People having oily skin suffer from acne, whiteheads and blackheads quite often so scrubbing become more essential. In our present study we formulated 3 different formulations F1, F2, F3 in gel form for oily skin by using turmeric, aloe vera, cinnamon, potato starch, activated charcoal powder, honey, green tea, lemon juice, onion, walnut shell, coconut oil, beet root juice powder, sodium lauryl sulphate, water and evaluated by using various parameters such as physical appearance, viscosity, pH, Spreadability, irritability, washability, stability studies and got fruitful results with all the tests. The scrub F2 was found to show excellent effects on controlling oil secretion, and preventing formation of new pimples. The herbal formulation F2 was having characteristic odour, reddish brown in color having, light, non-irritant to the skin and quite elegant. The powder was smooth to touch and in gel form it spreads satisfactorily. Thus, the formulated scrub F2 can be utilized efficaciously without a side effect which exfoliates and makes glowing skin.